(3JSjjQ hGbJUGO GdeDSSI s - (3fQLS(B, (3aQjhIs ((3GdLRdFQ(B:s (3OGQ GdHGMK ddfTQ hGdGTgGQ(B,s, 2023)
(3Cge eOGQS GdacQ GdJSjjQj hGdJfXjej, GdeDSSI JYQjagG, CfhGYgG hJWhQgG, GdGOGQI hGSJQGJjLjI GdeDSSI, hXGFa GdeDSSI, hGdCfXeI GdJfSjbjI ajgG, cPdc eLOOGJ JfGaSjI GdeDSSI(B.s
(3eQGLY U(B.172s
Keywords: (3GdGbJUGOs; (3JSjjQ GdeDSSIs